Substrate scope and stereocontrol in the Rh(II)-catalysed oxyamination of allylic carbamates - Unsworth, W; Lamont, S; Robertson, J (2014)
Application of a modified Du Bois protocol for rhodium-stabilised nitrenoid generation to a variety of allylic carbamates results in 4-acetoxymethyl-1,3-oxazolidin-2-one derivatives with moderate to high levels of stereocontrol. © 2014 Elsevier Ltd. All rights reserved.